A possible relationship between interannual variability in Antarctic ozone and the quasi-biennial oscillation - Garcia, Rolando R.; Solomon, Susan (Geophysical research letters, 1987)
Extra‐tropical temperatures, geopotential heights, and total ozone abundances are known to vary with the tropical Quasi‐Biennial Oscillation (QBO), although the details of the causal mechanisms linking the two regions are still a subject of debate. It is shown that total ozone amounts observed in Antarctica during 1979‐1986 exhibit year‐to‐year fluctuations that may be due to the influence of the QBO, with relatively low (high) values occurring during the westerly (easterly) phase. This suggests that the QBO should be taken into account when evaluating the amplitude and continuation of the long‐term trend in Antarctic total ozone. In particular, if the tropical QBO is in its westerly phase during October, 1987, an increase in total ozone at that time may be inconsistent with the continuation of the secular decrease observed since the 1970’s.